2019
DOI: 10.1590/1807-1929/agriambi.v23n12p959-965
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of lima bean subjected to salt and water stresses

Abstract: Under water deficit and/or salt stress conditions, crops suffer from several physiological disturbances, which lead to the reduction in growth and, consequently, decreases in their yields. Thus, the objective of this study was to evaluate the physiological responses of lima bean, cultivar Espírito Santo, under different irrigation water salinity associated to two water regimes. The experiment was carried out in the experimental area of the Universidade Federal do Ceará, Brazil, from September to November 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…Salt stress provides stomata closure and consequently reduced transpiration to prevent water loss to the medium (Pereira Filho et al, 2019). Negative effects of salinity were observed by Oliveira et al (2017), where they found that increasing irrigation water salinity reduced stomatal conductance values in the cowpea crop.…”
Section: Resultsmentioning
confidence: 95%
“…Salt stress provides stomata closure and consequently reduced transpiration to prevent water loss to the medium (Pereira Filho et al, 2019). Negative effects of salinity were observed by Oliveira et al (2017), where they found that increasing irrigation water salinity reduced stomatal conductance values in the cowpea crop.…”
Section: Resultsmentioning
confidence: 95%
“…The results show that the cultivars Branquinha, Espírito Santo and Orelha-de-vó adapted better compared to Manteiguinha. This morphophysiological adaptation may result in greater plant efficiency in photosynthetic processes and in the transport of organic solutes in plant tissues (PEREIRA FILHO et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The use of irrigated agriculture becomes fundamental for a safe production (Léllis et al, 2022;Lacerda et al, 2020). This practice becomes indispensable in regions that present a high climatic variability, as is the case of the semi-arid region of Brazil; however, the vast majority of water sources available for irrigation in this region present a high content of salts (Fernandes et al, 2016;Pereira et al, 2019;Dias et al, 2020).…”
Section: Introductionmentioning
confidence: 99%